Functional Walking Speed in Transtibial Prosthesis Users: Insights from Prosthesis Use Duration - Muhibbah Fatati; Dwi Setyawan; Prasetyo catur Utomo (Poltekkes Kemenkes Surakarta, 2026)
Background: Amputation of a lower limb has a detrimental effect on one's quality of life, psychological health, and physical health. Reduced physical capacity is one of the effects that contributes to physical health. As a result, the experience of using a prosthesis is essential for enhancing functional capacities to adjust to the social, professional, and family environments. The aim of this study was to determine the relationship between the length of prosthesis use and walking speed in transtibial prosthesis users. Methods: This study used a cross-sectional analytical observational design. A two-minute walk test was used to measure walking speed, and an observation sheet was used to assess usage duration. Purposive sampling was employed to recruit a total of 15 participants, and hypothesis testing was conducted using Spearman’s rank correlation. Results: The results showed that there was no significant correlation between walking speed and the duration of prosthesis use among transtibial prosthesis users (r = −0.314, p = 0.255). Conclusion: This study found no statistically significant relationship between the duration of prosthesis use and walking speed among transtibial prosthesis users. Walking speed is likely influenced by multiple factors, including age, stump length, muscle strength, and prosthesis condition. Therefore, rehabilitation strategies should adopt a comprehensive and individualized approach rather than relying solely on the duration of prosthesis use.